Genetic variability among Chlamydia trachomatis reference and clinical strains analyzed by pulsed-field gel electrophoresis. - Rodriguez, P (1994)
Pulsed-field gel electrophoresis (PFGE) was applied to Chlamydia trachomatis reference strains representing each of the 18 serovars and to 29 clinical isolates from genital specimens collected in Bordeaux, France, or Malmö, Sweden. Comparison of the fingerprint patterns of the reference strains revealed a high level of polymorphism of the total DNA when SmaI was used (14 profiles), whereas the other enzymes, Sse8387I and ApaI, showed fewer differences. Some serovars, considered to be closely related on the basis of their antigenic determinants located on the major outer membrane protein (MOMP), such as D and Da or I and Ia, were shown to be different after PFGE of their genomic DNAs. However, serovars B and Ba and serovars L2 and L2a had identical patterns after analysis with the three endonucleases. When applied to clinical isolates, which were typed by restriction fragment length polymorphism analysis of the MOMP gene, PFGE allowed the detection of intragenotype polymorphisms and showed the identity of two strains successively isolated from the same patient. This technique seems to be an efficient tool for epidemiological studies when used in addition to serotyping or genotyping by restriction fragment length polymorphism analysis of the MOMP gene.